The Influence of E-Booklet Media on Female Students' Knowledge and Attitudes Regarding Chronic Energy Deficiency - Sephia Fahridha; Ratnawati; Riska Mayang Saputri Ginting (Formosa Journal of Multidisciplinary Research, 2023)
The prevalence of KEK in East Kalimantan Province reached 12.4%, the highest prevalence based on age characteristics was found in the 15-19 year age group at 36.3%. The aim of this research is to determine the effect of nutrition education using e-booklet media on increasing female students' nutritional knowledge and attitudes regarding KEK. This type of research is Quasi Experimental with Pre-Post Test with Control Group Design. The research location is MTs Negeri Samarinda. There were 36 young women who participated in this research. Knowledge and attitude data were obtained from questionnaires. The results show that there is an influence of nutrition education using e-booklet media on increasing knowledge (p-value = 0.000) and attitudes (p-value = 0.000) of young women. There is no significant difference in the influence of e-booklet and leaflet media in increasing knowledge (p-value = 0.243) and attitudes (p-value = 0.189) of young women.